Pemanfaatan Teknologi Informasi dan Komunikasi dalam Bidang Pendidikan - bisyri, muhammad; Santoso, Aji; Hj. Maryati (LPPM STMIK ANTAR BANGSA, 2023)
The amazing development of IPTEK has been creating extraordinary benefits to advancement of human civilization. The benefits can be obtained in some fields such as scientific development, economics, education, politics, and many other fields. Based on the explanation above, it is interesting to examine the use of information and communication technology in various fields of human life, especially in the field of education so that the existence of information and communication technology can truly be realized and obtained by wider society. Education is recognized as the most important instrument in social and economic change. Improving the quality of education and expanding learning opportunities are the main problems faced by Southeast Asia countries. Thus, ICT is believed to be a strategic way to overcome these problems. In essence, ICT is the result of the process of teaching science and technology. Its existence as a the result of education makes big contribution and has big influence on the implementation of education. This can be seen from many educational practices which even depend on the existence of information technology and communication devices